VICTIM IMPACT STATEMENT DALAM SISTEM PERADILAN PIDANA: SEBUAH URGENSI HUKUM - Anggi Mustavia Maulani; Rusmilawati Windari (RechtIdee, 2022)
In criminal justice system, the impact of crime suffered by victims is less considered. In international sphere, the consideration of impact suffered by the victim is known as the Victim Impact Statement (VIS).  It is geared to determine the importance of VIS in the criminal justice system in Indonesia. This research is a normative legal research with statutory and conceptual approaches. All of the data are collected by using library and online search. Based on the research results, the urgency of VIS regulation is seen from 4 (four) basis, namely: (1) philosophical basis, the value of justice is the right of all people in equal treatment before the law; (2) the juridical basis, the limitations of the rules that explicitly regulate the rights of victims in the trial; (3) the political basis, the government has accommodated the Basic Principles of justice for victims of crime and abuse power 1985; (4) sociological basis, victims often experience injustice, VIS must be regulated to provide opportunities for victims to voice the impact of crimes suffered by them. The regulation of VIS will give space for victim involvement  in the judicial process and gaining satisfaction with the judge's decision.